Private social investment: the strategy and management of foundations and institutes - Gentil, Daniela; Ferreira, Gleriani; Rodrigues, Ivete (Revista de Administração da UFSM, 2019)
This article is the result of a qualitative research with multiple case studies in CSI portfolio companies with Foundation or Institute, and an exploratory research in articles; sustainability, integrated, or socioenvironmental reports; books; and websites on Private Social Investment and CSI (Corporate Sustainability Index). The return assesment of the PSI is increasingly required in the corporate world, because besides being positively ranked on the São Paulo Stock Exchange, it is critical for the maintenance of social projects, as well as to invest in new actions for the communities. The general objective of this study is to analyze how companies with Foundations and Institutes integrating the CSI portfolio evaluate the return of the PSI. The specific objectives are: i) to identify strategical policies and guidelines for PSI application; ii) analyze the leadership involvement with the PSI decisions; iii) identify possible impacts of PSI actions on the reputational image of the companies. iv) identify the focal point of action; v) check how the community needs are assessed; vi) check how the PSI impacts are evaluated. Among other relevant conclusions, it was found that the way in which PSI management is carried out, expresses the alignment of the sustainability to the business strategy. The study provides scholarly and practical contributions, by highlighting that the PSI actions are important in terms of the reputational image of the companies.